Pathogenic Mechanisms and Host Interactions in Staphylococcus epidermidis Device-Related Infection - Sabaté Brescó, Marina; Harris, Llinos G.; Thompson, Keith; Stanic, Barbara; Morgenstern, Mario; O'Mahony, Liam; Richards, R. Geoff; Moriarty, T. Fintan (Frontiers in Microbiology, 2017)
Staphylococcus epidermidis is a permanent member of the normal human microbiota, commonly found on skin and mucous membranes. By adhering to tissue surface moieties of the host via specific adhesins, S. epidermidis is capable of establishing a lifelong commensal relationship with humans that begins early in life. In its role as a commensal organism, S. epidermidis is thought to provide benefits to human host, including out-competing more virulent pathogens. However, largely due to its capacity to form biofilm on implanted foreign bodies, S. epidermidis has emerged as an important opportunistic pathogen in patients receiving medical devices. S. epidermidis causes approximately 20% of all orthopedic device-related infections (ODRIs), increasing up to 50% in late-developing infections. Despite this prevalence, it remains underrepresented in the scientific literature, in particular lagging behind the study of the S. aureus. This review aims to provide an overview of the interactions of S. epidermidis with the human host, both as a commensal and as a pathogen. The mechanisms retained by S. epidermidis that enable colonization of human skin as well as invasive infection, will be described, with a particular focus upon biofilm formation. The host immune responses to these infections are also described, including how S. epidermidis seems to trigger low levels of pro-inflammatory cytokines and high levels of interleukin-10, which may contribute to the sub-acute and persistent nature often associated with these infections. The adaptive immune response to S. epidermidis remains poorly described, and represents an area which may provide significant new discoveries in the coming years.